High performance teamwork training and systems redesign in outpatient oncology. Issue 5 (24th January 2013) - Bunnell, Craig A; Gross, Anne H; Weingart, Saul N; Kalfin, Michael Jason; Partridge, Ann; Lane, Sharon; Burstein, Harold J; Fine, Barbara; Hilton, Nancy A; Sullivan, Clare; Hagemeister, Erin E; Kelly, Anne E; et al.
Abstract : Background: Oncology care is delivered largely in ambulatory settings by interdisciplinary teams. Treatments are often complex, extended in time, dispersed geographically and vulnerable to teamwork failures. To address this risk, we developed and piloted a team training initiative in the breast cancer programme at a comprehensive cancer centre. Methods: Based on clinic observations, interviews with key staff and analyses of incident reports, we developed interventions to address four high-risk areas: (1) miscommunication of chemotherapy order changes on the day of treatment; (2) missing orders on treatment days without concurrent physician appointments; (3) poor follow-up with team members about active patient issues; and (4) conflict between providers and staff. The project team developed protocols and agreements to address team members' roles, responsibilities and behaviours. Results: Using a train-the-trainer model, 92% of breast cancer staff completed training. The incidence of missing orders for unlinked visits decreased from 30% to 2% (p<0.001). Patient satisfaction scores regarding coordination of care improved from 93 to 97 (p=0.026). Providers, infusion nurses and support staff reported improvement in efficiency (75%, 86%, 90%), quality (82%, 93%, 93%) and safety (92%, 92%, 90%) of care, and more respectful behaviour (92%, 79%, 83%) and improved relationships among team members (91%, 85%, 92%). Although most clinicians reported a decrease in non-communicated changes, there was insufficient statistical power to detect a difference. Conclusions: Team training improved communication, task coordination and perceptions of efficiency, quality, safety and interactions among team members as well as patient perception of care coordination.